AGC family kinase of Entamoeba histolytica: Decoding the members biochemically. - Azhar Ahmad; Vikas Kumar; Tushar Kushwaha; Akash Kumar; Deepak Sehgal; Krishna K Inampudi; Somlata (PLoS Pathogens)
Entamoeba histolytica, a protozoan parasite, is the causative agent of amoebiasis, which is a significant global health concern. The virulence mechanisms underlying its pathogenicity are multifaceted and complex. However, endocytic processes and motility are well accepted virulence determinants. As previously reported, an AGCK family kinase, EhAGCK1 to be involved in trogocytosis exclusively while another one from same family named EhAGCK2 participates in all actin dependent endocytic processes. As the kinase dead mutants of EhAGCK1 showed significant defect in destruction of live host cells and also the localisation pattern of same is distinguishable from EhAGCK2. From observations so far, it appears that former initiates a distinguishable signaling cascade. In this work, we have demonstrated distinct biochemical properties of kinases involved in related yet distinguishable endocytic processes for the first time. Our biochemical characterization highlights distinct ion dependency of EhAGCK1 along with substrate specificity. We also show upstream activator of these kinases, 3-phosphoinositide dependent kinase 1 (PDK1) activity and its role in activating the kinase activity. The kinases exhibit property of autophosphorylation, and which may regulate the kinase activity subsequently. Summarily, these studies show that EhAGCK1 and EhAGCK2 show distinct biochemical properties which further confirm their unique role in related endocytic processes of trogocytosis and phagocytosis.